The Role of Lifestyle in Moderating the Influence of Financial Literacy and Ease of Use on the Consumptive Behavior PayLater Users on Generation Z in Surabaya City - Sakti, Angela Tiara; Anwar, Muhadjir (Dinasti Publisher, 2025)
Shopee PayLater is a fintech service frequently used nowadays, particularly among Generation Z in Surabaya. The ease of using this service makes many of Generation Z use it for consumptive purposes, but enough financial capability does not follow it. This study seeks to examine how financial literacy and user-friendliness impact consumer spending tendencies, with lifestyle serving as a moderating variable. This research adopts quantitative methods using primary data. Respondents in this research were Generation Z users of Shopee PayLater in Surabaya. A total of 112 respondents were selected through a non-probability sampling technique, then analyzed with SEM-PLS. The results showed that Financial Literacy has a positive influence on Consumptive Behavior. The level of ease of use contributes significantly to individual consumption patterns. Lifestyle acts as a factor that strengthens the relationship between financial literacy and consumer behavior. Conversely, lifestyle does not have a moderating effect on the relationship between ease of use and consumer behavior among Shopee PayLater consumers in Surabaya.